EFFECT IN TELEVISION ADVERTISING DELIVERY DECISION TO BUY COMMUNITY IN SUB TEMPEL, DISTRICT SLEMAN - Purwa A., R. Fajar Sidik; Lastari, SE., MM, Siwi; Murdo, M.Si, Drs. Yuri (Management, 2010)
Advertising is one of the variables from the campaign or promotion mix in addition to personal selling, publicity and sales promotion. Advertising should be used as part of efforts to introduce products to consumers that the company can be considered to increase sales volume. Of course, the ads shown to be able to attract consumers so that consumers want to listen, see it, know what they mean and know what is advertised and eventually want to buy the advertised product. The purpose of this study was to determine the effect Shampoo ads on television against the decision to buy the community in District Tempel, Sleman regency. Based on the results of a study of 100 respondents conducted in communities in the District of Paste, shows that, if the regression coefficient of Impression Ad Products Shampoo for 0603, if there is an increase or decrease by 1% it will increase or decrease the Purchase Decision of 0603% with a record of other variables remain . While the regression coefficient of Quality for 0316, if there is an increase or decrease by 1% then it will change the Purchase Decision of 0316% with a record of the other variables fixed. And for the price regression coefficient of 0.06801, if there is an increase or decrease by 1% it will increase the Purchase Decision of 0.06801% with a record of the other variables fixed. Based on the calculation of coefficient of determination of the result for 0967, which means Buying Decision variables are influenced by variables Communities Served Products Shampoo Ad Based on the test results obtained correlation coefficient a significant correlation, the correlation between the decision to buy the community by serving ads Shampoo is a 0891 product. Based on the significant test, no significant relationship between Ad Insertion to the Decision to Buy Shampoo Products Society This result means that, there is a relationship between the delivery of products to the decision to purchase shampoo advertisement communities. Keywords: Shampoo, Consumer.